Photon management for enhanced open-circuit voltage in nanostructured solar cells. (29th September 2015) - Sandhu, S; Yu, Z; Fan, S
Abstract: We review the recent progress on using pure photonic engineering for voltage enhancement of nanostructured solar cells. These works use a detailed balance analysis for the current–voltage modeling of their devices, while taking into account of intrinsic material nonidealities to determine their fundamental limiting performances. The physics of voltage enhancement in these nanostructures is elucidated and shown to be related to the suppression of thermal emission in the immediate vicinity of the material electronic bandgap. We also review a recent work on using thermal emission suppresion in a single material tandem cell configuration to overcome the Shockley–Queisser limit.